A Comparison of the Effect of Probiotic Lactobacillus Reuteri and Syrup-Caraway Mixture in the Treatment of Infantile Colic: A Randomized Clinical Trial Study - Mehrdad Mirzarahimi; Afshan Sharghi *; Ashraf Kheiri (Lorestan University of Medical Sciences, 2021)
Background and Aim: Infantile colic is a relatively common behavioral syndrome in infancy. The main mechanism of colic is still unknown and no effective treatment is indicated for it. Recently, a relation between colic-infected children and the microbial balance changes in their intestines has been reported. Accordingly, we decided to compare the effect of probiotics with the syrup-caraway mixture on colic. Materials and Methods: In this clinical trial study, 86 infants with colic were included. Data were collected by a checklist including the duration of crying, severity of crying, crying frequency and complications of treatment which were completed during the course of the treatment through the follow-up of the infants. Infants were randomly divided into two equal-size groups based on random block design. The first group received probiotic lactobacillus reuteri (17938 DSM), and the second group received syrup-caraway mixture. The collected data were analyzed by statistical methods in SPSS version 24. Results: The mean age of the patients was 30.58±14.18 days. Two groups were similar according to age, sex, birth weight, parental education level, history of atopy in the family, history of colic in previous children and crying at presentation. There was no difference between the groups based on the crying frequency, severity of crying and duration of crying on the 7th and 15th days. Moreover, there was no difference in terms of drug side effects between two groups in the seventh and fifteenth days of treatment. Conclusion: Both probiotics and syrup-caraway mixture are effective in the treatment of colic in infancy.